2017
DOI: 10.1007/s40262-017-0544-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morbid Obesity on the Pharmacokinetics of Morphine, Morphine-3-Glucuronide, and Morphine-6-Glucuronide

Abstract: IntroductionObesity is associated with many pathophysiological changes that may result in altered drug metabolism. The aim of this study is to investigate the influence of obesity on the pharmacokinetics of morphine, morphine-3-glucuronide (M3G), and morphine-6-glucuronide (M6G) through a combined analysis in morbidly obese patients and non-obese healthy volunteers.MethodsIn this analysis, data from 20 morbidly obese patients [mean body mass index 49.9 kg/m2 (range 37.6–78.6 kg/m2) and weight 151.3 kg (range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
0
32
0
2
Order By: Relevance
“…One study noted decreased clearance of active morphine metabolites in morbidly obese compared to normal weight healthy volunteers, despite normal elimination of the parent compound. The clinical importance of this finding is unknown but could be of consequence with sustained dosing [23]. Pharmacodynamic alterations such as increased opioid sensitivity have also been described in select populations (e.g., geriatrics, obstructive sleep apnea) which can further increase the risk for respiratory depression [24,25].…”
Section: Analgesia Opioidsmentioning
confidence: 99%
“…One study noted decreased clearance of active morphine metabolites in morbidly obese compared to normal weight healthy volunteers, despite normal elimination of the parent compound. The clinical importance of this finding is unknown but could be of consequence with sustained dosing [23]. Pharmacodynamic alterations such as increased opioid sensitivity have also been described in select populations (e.g., geriatrics, obstructive sleep apnea) which can further increase the risk for respiratory depression [24,25].…”
Section: Analgesia Opioidsmentioning
confidence: 99%
“…Many patients who require postoperative treatment of pain are obese and/or have diabetes mellitus. Previous studies have reported the effect of obesity and/or diabetes mellitus on the pharmacokinetics of many drugs [57]. Tramadol is an analgesic used for treating moderate to moderately severe acute and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies on pharmacokinetics of morphine, 7,8 It was determined that 15 patients for each group were required for the study to have type I error of 0.05 and a power of 80%, using a confidence interval of 95%. We recruited 20 per group to account for patient drop out, random errors, and additional comparisons.…”
Section: Discussionmentioning
confidence: 99%